Seeing green: Mere exposure to money triggers a business decision frame and unethical outcomes - Kouchaki, Maryam; Smith-Crowe, Kristin; Brief, Arthur P.; Sousa, Carlos (Organizational behavior and human decision processes, 2013)
► We examine the likelihood of unethical outcomes after exposure to money primes. ► Individuals primed with money are more likely to demonstrate unethical behavior. ► Individuals primed with money are more likely to adopt a business decision-frame. ► Money primes trigger a business decision-frame leading to greater unethical behavior. Can mere exposure to money corrupt? In four studies, we examined the likelihood of unethical outcomes when the construct of money was activated through the use of priming techniques. The results of Study 1 demonstrated that individuals primed with money were more likely to demonstrate unethical intentions than those in the control group. In Study 2, we showed that participants primed with money were more likely to adopt a business decision frame. In Studies 3 and 4, we found that money cues triggered a business decision frame, which led to a greater likelihood of unethical intentions and behavior. Together, the results of these studies demonstrate that mere exposure to money can trigger unethical intentions and behavior and that decision frame mediates this effect.